2010
DOI: 10.1016/j.bbrc.2010.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AMP-activated-protein-kinase (AMPK) in neuronal amyloidogenesis

Abstract: AMP-activated-protein-kinase (AMPK) is a key sensor and regulator of cellular and whole-body energy metabolism and plays a key role in regulation of lipid metabolism. Since lipid metabolism has been implicated in neuronal amyloid-β (Aβ) homeostasis and onset of Alzheimer's disease, we investigated the involvement of AMPK in neuronal lipid metabolism and Aβ production. We observed in cultured rat cortical neurons that Aβ production was significantly reduced when the neurons were stimulated with AMPK activator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 19 publications
1
53
0
2
Order By: Relevance
“…It is reported that AMPK activation reduces amyloid ␤ production in rat cortical neurons (24) and that leptin and resveratrol reduce amyloid ␤ levels and Tau phosphorylation through AMPK activation (25)(26)(27). In contrast, AMPK can directly phosphorylate Tau, and amyloid ␤-induced increases in Tau phosphorylation require AMPK-activated Ca 2ϩ /calmodulin-dependent protein kinase kinase ␤ (28).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…It is reported that AMPK activation reduces amyloid ␤ production in rat cortical neurons (24) and that leptin and resveratrol reduce amyloid ␤ levels and Tau phosphorylation through AMPK activation (25)(26)(27). In contrast, AMPK can directly phosphorylate Tau, and amyloid ␤-induced increases in Tau phosphorylation require AMPK-activated Ca 2ϩ /calmodulin-dependent protein kinase kinase ␤ (28).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Vingtdeux et al [130] demonstrated that there was abnormal accumulation of activated AMPK in tangle-and pretangle-bearing neurons in AD. AMPK signaling can regulate tau protein phosphorylation and amyloidogenesis [131]. AMPK is also a potent activator of autophagic degradation, which seems to be suppressed in AD.…”
Section: Undetermined Pathways In Samp8 That Could Addmentioning
confidence: 99%
“…74,78 In the same way, many studies have described the divergent evidence about the involvement of AMPK in brain tumors and ischemic stroke. The presence of contradictory results indicates that further investigations are needed to better dissect the molecular mechanisms linking AMPK activity and the development of CNS diseases.…”
Section: Rosso Et Almentioning
confidence: 94%
“…On the contrary, Aβ peptide levels are increased when AMPKα2 is knocked out, thus indicating the crucial involvement of AMPK in amyloidogenesis. 74 AMPK controls Aβ generation through the modulation of neuronal cholesterol and sphingomyelin levels, which regulate APP distribution in lipid rafts. 67 In addition, leptin-induced AMPK activation is associated with a reduction in Tau phosphorylation.…”
Section: Ampk In Admentioning
confidence: 99%